Bone-graft interface in New Zealand White rabbit’s model: A novel Malaysian-made biomaterial, “osteopaste” - Zakaria@Mohamad, Zamzuri; Che Seman, Che Nor Zarida; Zulkifly, Ahmad Hafiz; Buyong, Zunariah; Awang, Mohd Shukrimi; Mohd Yusof, Nazri; Md Ralib, Azrina (2020)
Injectable self-hardened synthetic bone cement (Osteopaste) was developed from limestone for the purpose to promote healing of bone fracture or in reconstructed bone defects. Excellent biocompatibility of biomaterial results in close cellular contact with biomaterial surface. The aim of this study was to evaluate the bone cell response produced at the bone-biomaterial interface using light microscopy (LM) and scanning electron microscopy (SEM). Osteopaste was implanted in a critical size defect model in rabbits’ tibiae and then, compared with commercialized bone graft; JectOS (calcium phosphate) and MIIG-X3 (calcium sulphate). The animals were sacrificed at 6, 12 and 24 weeks post-surgery and bone tissues containing biomaterials were harvested. The specimens were then processed for viewing under LM and SEM to access the histological analysis, surface of biomaterials and biomaterial-bone interface. This visualization showed that no intervening soft tissue seen between new bone and Osteopaste which enable osteoblast cells adhered and spread on the surface of Osteopaste compared with JectOS and MIIG-X3. In conclusion, Osteopaste is biocompatible, osteoconductive and showed osteointegration with surrounding host bone to support ingrowth of new bone.